2010
DOI: 10.1002/ceat.201000015
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Temperature De‐NOx by Selective Catalytic Reduction Based on Iron‐Based Catalysts

Abstract: Low-temperature De-NO x technology is a new topic in the area of flue gas treatment. This paper presents experimental studies on selective catalytic reduction (SCR) of NO x from synthetic flue gas over iron-based catalysts with ammonia in a fluidized reactor. The iron-based catalysts used in the experiments are particles of Fe 3 O 4 and c-Fe 2 O 3 , and they are analyzed by X-ray diffraction (XRD) and Mössbauer spectroscopy, before and after reaction. It is observed that the efficiency of De-NO x with c-Fe 2 O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 31 publications
0
28
0
3
Order By: Relevance
“…However, further increases of the precursor concentration led to a decrease of the Fe loading content. As Yao et al reported, Fe 2 O 3 provided a much higher deNO x efficiency than the other FeO x species. Thus, we speculate that the excellent deNO x performance for Fe20/ASC may be ascribed to the larger quantity of surface Fe 3+ ions.…”
Section: Resultsmentioning
confidence: 84%
“…However, further increases of the precursor concentration led to a decrease of the Fe loading content. As Yao et al reported, Fe 2 O 3 provided a much higher deNO x efficiency than the other FeO x species. Thus, we speculate that the excellent deNO x performance for Fe20/ASC may be ascribed to the larger quantity of surface Fe 3+ ions.…”
Section: Resultsmentioning
confidence: 84%
“…This mature system displays adequate activity typically at 300-400 8C, but it is still not satisfactory with respect to the volatility and toxicity of VO x and the easy deactivation. [1][2][3] Attracted by the inherently environmentally benign character and the prominent thermal stability, ferric oxides have long been explored to catalyze selective reduction of NO x with ammonia, [3][4][5][6][7][8] but no significant progress has been achieved so far. Ferric oxides commonly suffer from the insufficient activity at low temperatures and the severe deactivation induced by H 2 O and SO 2 that are permanently and abundantly present in the exhaust.…”
mentioning
confidence: 99%
“…

Die selektive katalytische Reduktion (SCR) von Stickstoffoxiden (NO x ) mit NH 3 ist heutzutage die aussichtsreichste Technik zur Beseitigung derartiger Verbindungen, die bei der Verbrennung fossiler Brennstoffe entstehen. [1][2][3] Begünstigt durch ihre Umweltverträglichkeit und ausgeprägte thermische Stabilität wurden Eisenoxide seit Langem für die SCR von NO x mit NH 3 untersucht, [3][4][5][6][7][8] bislang konnte jedoch kein Durchbruch erzielt werden, da Eisenoxide bei niedrigen Temperaturen üblicherweise eine unzureichende Aktivität aufweisen und stark durch H 2 O und SO 2 , die permanent und allgegenwärtig im Abgas vorhanden sind, desaktiviert werden. Das ausgereifte System zeigt typischerweise bei 300-400 8C eine hinreichende Aktivität, ist aber wegen der Flüchtigkeit und Giftigkeit von VO x und der raschen Desaktivierung nicht zufriedenstellend.

…”
unclassified